Short‐term skin reactions following use of N95 respirators and medical masks - Hua, Wei; Zuo, Ying; Wan, Ruoyu; Xiong, Lidan; Tang, Jie; Zou, Lin; Shu, Xiaohong; Li, Li (Contact dermatitis, 2020)
Background In the context of the COVID‐19 pandemic, cases of adverse skin reactions related to the wearing of masks have been observed. Objectives To analyze the short‐term effects of N95 respirators and medical masks, respectively, on skin physiological properties and to report adverse skin reactions caused by the protective equipment. Methods This study used a randomized crossover design with repeated measurements. Twenty healthy Chinese volunteers were recruited. Skin parameters were measured on areas covered by the respective masks and on uncovered skin 2 and 4 hours after donning, and 0.5 and 1 hour after removing the masks, including skin hydration, transepidermal water loss (TEWL), erythema, pH, and sebum secretion. Adverse reactions were clinically assessed, and perceived discomfort and non‐compliance measured. Results Skin hydration, TEWL, and pH increased significantly with wearing the protective equipment. Erythema values increased from baseline. Sebum secretion increased both on the covered and uncovered skin with equipment‐wearing. There was no significant difference in physiological values between the two types of equipment. More adverse reactions were reported following a N95 mask use than the use of a medical mask, with a higher score of discomfort and non‐compliance. Conclusions This study demonstrates that skin biophysical characters change as a result of wearing a mask or respirator. N95 respirators were associated with more skin reactions than medical masks.